Determinant of Mental Emotional Disorder in Adolescent: A Cross-Sectional Study - Dondo, Marisa Lestary; Riskiyani, Shanti; Suriah,; Syafar, Muhammad; Wahiduddin,; Jafar, Nurhaedar (International Journal of Statistics in Medical Research, 2023)
Objective: Adolescence is a critical period for experiencing mental disorders because this age is a transition from adolescence to adulthood, this period is also a determinant of one's mental health in the future. According to survey data from the Indonesia National Adolescent Mental Health Survey (I-NAMHS), which examined the prevalence of adolescent mental disorders in the country reveal that 1 out of 20 (5.5%) adolescents aged 10-17 years in Indonesia were diagnosed with a mental disorder. This study aimed to investigate the degree of risk of poor self-concept clarity, low self-esteem, a lack of peer support, and victims of bullying on mental-emotional disorders incidence in adolescents. Methods: This research is an observational study using a cross-sectional design. The sample in this study were high school students aged 15-18 years (n = 390) who were randomly selected from four high schools in Kotamobagu City, North Sulawesi Province, Indonesia. The data in this study were analyzed through the Chi-Square test and multiple regression test using the SPSS version 22.0. Results: This research shows that poor self-concept clarity (adj OR = 5.760; 95%CI = 3.173-10.458; p<0.001), low self-esteem (adj OR =3.647; 95%CI = 1.950-6.818; p<0.001), and victims of bullying (adj OR = 4.204; 95% CI =1.525-11.589; p=0.006) are related to adolescents’ mental-emotional disorders. Conclusions: It was concluded that the factors that influence mental-emotional disorders in adolescents are poor self-concept clarity, low self-esteem, and being a victim of bullying.